Chart of the N. W. Coast of America and the N. E. Coast of Asia. (1794) - Roberts, Henry; Delarochette, Louis. (London : Wm. Faden, Geographer to the King, 1794)
1 map : col.; 58 x 80 cm. Scale: 1 inch = approximately 140 British miles, or 1 inch = 20 Nautical Leagues. Chart of sea routes explored by Captain Cook in the years 1778 and 1779, first published in 1784. Includes Native American place names and cited information from others' maps and charts. Areas outlined in red are British discoveries, blue are Russian, and yellow are Spanish. Includes the Strait of Juan de Fuca and "mountains covered in snow in August," the supposed route of the American sloop the Washington, and the area assumed to be the Sea of the West. Engraved by W. Palmer, No. 128 Chancery Lane. "The Interesting Discoveries made by British and American Ships, since the first publication of this Chart in 1784, Together with the Hydrographical Materials lately procured from St. Petersburg and other places, have enabled Mr. De la Rochette to lay down the Numerous Improvements which appear in this Present Edition. Charing Cross, January 1st, 1784, W. Faden."